The new accountability : environmental responsibility across borders - Mason, Michael, 1966- (London : Earthscan, 2005)
'Drawing on case studies, this book provides a fresh understanding of democratic accountability for transboundary and global harm and argues that environmental responsibility should be established in open public discussions about harm and risk'--Provided by publisher
Includes bibliographical references (p. [179]-196) and index
Keywords: Environmental protection -- International cooperation; Environmental policy -- International cooperation; Environmental responsibility